Human Organ Markets and Inherent Human Dignity. Issue 1 (1st January 2014) - MacKellar, Calum
Abstract It has been suggested that human organs should be bought and sold on a regulated market as any other material property belonging to an individual. This would have the advantage of both addressing the grave shortage of organs available for transplantation and respecting the freedom of individuals to choose to do whatever they want with their body parts. The old arguments against such a market in human organs are, therefore, being brought back into question. The article examines the different arguments both in favour and against the sale of human organs. It concludes that the body and any of its elements is a full expression of the whole person. As such, they cannot have a price if the individual is to retain his or her full inherent dignity and if society is to retain and protect this very important concept.